2017
DOI: 10.1111/1748-5967.12271
|View full text |Cite
|
Sign up to set email alerts
|

Comparative damage and digestive enzyme activity of Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) on 12 tomato cultivars

Abstract: The damage caused by the tomato leaf miner Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) to 12 tomato cultivars was investigated under greenhouse conditions. The 2 cultivars Korral and CH Falat experienced lower damage in terms of all parameters investigated, whereas the cultivars Valouro and Cal JN3 were categorized as the most susceptible host plants. The larvae feeding on CH Falat and Korral cultivars reached the lowest final weight (1.82 and 1.93 mg, respectively), whereas those reared on the Valouro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…This might be because the lower activities of amylase could meet the need for nutrition. Shahbaz et al (2019) found that Tuta absoluta (Meyrick) had the highest body weight but the lowest enzyme activity on susceptible tomato cultivars. The present study also found that there was no significant change in tryptase activity in the second instars following transfer to kidney bean plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be because the lower activities of amylase could meet the need for nutrition. Shahbaz et al (2019) found that Tuta absoluta (Meyrick) had the highest body weight but the lowest enzyme activity on susceptible tomato cultivars. The present study also found that there was no significant change in tryptase activity in the second instars following transfer to kidney bean plants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Helicoverpa armigera (Hübner) regulates the levels of digestive enzymes in response to the macromolecular composition of its diet, allowing it to obtain better nourishment and avoid toxicity due to nutritional imbalance (Kotkar et al, 2009; Simon et al, 2015). When feeding on a host plant with higher nutrient content, some enzymes significantly increased their activities to ensure rapid growth (Wright et al, 2006; Zhang et al, 2009), whereas the activity of other enzymes did not change significantly (Kotkar et al, 2009; Shahbaz et al, 2019). The differences in activity of digestive enzymes among host plants reflect the mechanism of insect physiological regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Tuta absoluta larvae attack almost all aerial parts of tomato plants, resulting in ~80-100% yield losses if left uncontrolled [73]. Larval feeding also reduces fruit quality through creating pin holes prone to secondary attack by pathogens, rendering them unmarketable [74].…”
Section: Economic Impact Of Tuta Absoluta In Africamentioning
confidence: 99%
“…The net reproductive rate as well as the intrinsic rate of population growth were both higher on 'Bravo' than on 'Tex 317'. Larvae feeding on the 'Valouro' cultivar, classified as highly susceptible to T. absoluta infestation, showed the lowest proteolytic and amylolytic activity and reached the highest body weight (3.42 mg) compared to the 'Korral' cultivar (Shahbaz et al, 2017). Sadeghinasab et al (2017) indicated that Km and Vmax values for α-amylase, the specific activity of α-/ß-glucosidases and α/ß-galactosidases, obtained for T. absoluta fourth instar larvae differ among tested tomato cultivars ('Kingston', 'Riogrande', 'Super Luna', 'Super Chief', 'Super strain B' and 'Calj').…”
Section: Host Plants and Tuta Absoluta Controlmentioning
confidence: 98%
“…Tuta absoluta cultivar resistance is likely associated with the diversity and abundance of glandular trichomes (Campos et al, 2009;Khederi et al, 2014;Shahbaz et al, 2017). The length and density of glandular trichomes are negatively correlated with T. absoluta damage (Darbain et al, 2016).…”
Section: Host Plants and Tuta Absoluta Controlmentioning
confidence: 99%